The Paradox of Law Enforcement: Corporations Escaping Corruption Charges: Study of Decision No. 40/Pid.Sus-TPK/2024/PN Jkt.Pst - Ahmad Nur Shadiq; Hasan Akmal Rohmatino (The Digest: Journal of Jurisprudence and Legisprudence, 2025)
Indonesia, as a country committed to the principle of the rule of law, continues to encounter major obstacles in the enforcement of laws related to corporate corruption. The corporate sector is particularly prone to corrupt practices due to the large scale of financial transactions and the involvement of multiple stakeholders. This research focuses on the Central Jakarta District Court Decision No. 40/Pid.Sus-TPK/2024/PN Jkt.Pst, which concerns allegations of corruption involving five major companies in the crude palm oil (CPO) export sector. In its ruling, the panel of judges declared the defendants not legally accountable (onslag van alle rechtsvervolging), even though their actions were proven to have resulted in state losses of Rp1.6 trillion. The study utilizes a normative juridical method through a legislative and case study approach to analyze the rationale behind the court’s decision and its implications for the enforcement of corporate law. The findings indicate that the judges overlooked both formal and material elements of the offense, which should have been sufficient to establish the occurrence of corruption. This approach creates legal inequality, weakens justice, and provides corporations with room to evade legal accountability. Therefore, comprehensive reform of the criminal justice system is necessary, including strengthening regulations, establishing clear jurisprudence, and enhancing the integrity of judicial institutions to ensure the fair and equal enforcement of the rule of law.